Pelanggaran Hak Asasi Manusi dalam Proyek Gibe III di Ethiopia Tahun 2006-2015 - Sari, Yunita Arum; Windiani, Reni (Journal of International Relations, 2020)
The construction of the Gilgel Gibe III dam in 2006-2015 by the Ethiopian government as an effort to deal with the drought and to improve the people's welfare, has raised many issues. A number of human rights violations to indigenous peoples such as violence, rape, murder, ill-treatment, and forced displacement (villagization) were indicated during the development period, also resulting a number of environmental impacts. This study uses qualitative methods to explain the factors behind the government's actions. These factors are analyzed to find out what rights have been violated by the Ethiopian government. To answer the incident, the writer uses the theory of natural rights, green criminology, and legal responsibility. The results found that the government underestimated and lacked respect for the rights of minority tribes such as basic rights, the right to participate in development, the right to development information, and the right to land. Furthermore, it can be said that number of actions by the Ethiopian government as a crime against human rights. Therefore, decisive action as warning or sanction to the Ethiopian government are needed.